K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

24 tháng 9 2018

\(5:\frac{1}{x}+6:\frac{1}{x}-x=\frac{20}{3}\Leftrightarrow\left(5+6\right):\frac{1}{x}-x=\frac{20}{3}\)

\(\Leftrightarrow11:\frac{1}{x}=\frac{20}{3}\Leftrightarrow\frac{1}{x}=11:\frac{20}{3}\)

\(\Leftrightarrow\frac{1}{x}=\frac{33}{20}\Leftrightarrow1.20=x.33\Leftrightarrow20=33x\)

\(\Leftrightarrow x=20:33\Leftrightarrow x=\frac{20}{33}\)

2 tháng 7 2016

a) 3+2*x=15

2x=15-3

2x=12

x=12:2

x=6

Vậy x=6

b) 24-x=19

x=24-19

x=5

Vậy x=5

c) 29x-13=45

29x=45+13

29x=58

x=58:29

x=2

Vậy x=2

d) 5x-17=38

5x=38+17

5x=55

x=55:5

x=11

Vậy x=11

e) 50-2(x+1)=20

2(x+1)=50-20

2(x+1)=30

x+1+30/2

x+1=15

x=15-1=14

Vậy x=14

f) 

3 tháng 1 2019

lồn chó sủa

15 tháng 8 2020

Gyug : Hãm loz bn êy

12 tháng 6 2018

\(\left(\frac{3}{5}-x\right)+\frac{13}{20}=\frac{5}{6}\)

\(\frac{3}{5}-x=\frac{5}{6}-\frac{13}{20}\)

\(\frac{3}{5}-x=\frac{11}{60}\)

\(x=\frac{3}{5}-\frac{11}{60}\)

\(x=\frac{5}{12}\)

\(\left(x-\frac{1}{2}\right)\cdot\frac{5}{3}=\frac{7}{4}-\frac{1}{2}\)

\(\left(x-\frac{1}{2}\right)\cdot\frac{5}{3}=\frac{5}{4}\)

\(x-\frac{1}{2}=\frac{5}{4}:\frac{5}{3}\)

\(x-\frac{1}{2}=\frac{3}{4}\)

\(x=\frac{3}{4}+\frac{1}{2}\)

\(x=\frac{5}{4}\)

12 tháng 6 2018

( 3/5 - x ) + 13/20 = 5/6

  3/5 - x                = 5/6 - 13/20

  3/5 - x                = 89/60

          x                = 3/5 - 89/60

          x                = 25/12

( x - 1/2 ) x 5/3 = 7/4 - 1/2

( x - 1/2 ) x 5/3 = 5/4

 x - 1/2             = 5/4 : 5/3

 x - 1/2             = 35/12

 x                     = 35/12 + 1/2

 x                     = 41/12

24 tháng 7 2017

a)\(\left(x+3\right)\times5+1=20\Leftrightarrow5x+15=19\)

\(\Leftrightarrow5x=4\Leftrightarrow x=\frac{4}{5}\)

b)sai đề

c)\(2\frac{3}{7}\times x+1\frac{5}{4}=5\frac{3}{42}\)\(\Leftrightarrow\frac{17}{7}\times x+\frac{9}{4}=\frac{71}{14}\) \(\Leftrightarrow\frac{17}{7}\times x+\frac{63}{28}=\frac{142}{28}\)

\(\Leftrightarrow\frac{17}{7}\times x=\frac{79}{28}\Leftrightarrow x=\frac{17}{7}:\frac{79}{28}\) \(\Leftrightarrow x=\frac{17}{7}\times\frac{28}{79}\Leftrightarrow x=\frac{476}{553}=\frac{68}{79}\)

d)\(10\frac{2}{3}-x:\frac{6}{7}=8\frac{1}{3}-6\frac{2}{7}\Leftrightarrow\frac{32}{3}-x:\frac{6}{7}=\frac{25}{3}-\frac{44}{7}\) \(\Leftrightarrow\frac{224}{21}-x:\frac{6}{7}=\frac{75}{21}-\frac{132}{21}\Leftrightarrow-\frac{57}{21}-\frac{224}{21}\)

\(\Leftrightarrow-x:\frac{6}{7}=-\frac{281}{21}\Leftrightarrow-x=-\frac{281}{21}\times\frac{6}{7}\) \(\Leftrightarrow-x=-\frac{1686}{147}\Leftrightarrow x=\frac{562}{49}=11\frac{23}{49}\)

28 tháng 7 2018

a,3x-3+6x-12=5

9x-15=5

9x=20

x=20/9

b,3x-6+6x-6=6

9x-12=6

9x=18

x=2

c,4x+4+5x+10=3x+20

9x+14=3x+20

9x-3x=6

6x=6

x=1

28 tháng 7 2018

a) 3.(x-1) + 6.(x-2) = 5

3.x - 3 + 6.x - 12 = 5

9.x - 15 = 5

9.x = 5 + 15

9.x = 20

x = \(\frac{20}{9}\)

Vậy x = \(\frac{20}{9}\)

b) 3.(x-2) + 6.(x-1) = 6

  3.x - 6 + 6.x - 6 = 6

9.x - 12 = 6

9.x = 6 + 12

9.x = 18

x = 18 : 9

x = 2

Vậy x = 2

c) 4.(x+1) + 5.(x+2) = 3.x +20

4.x +4 +5.x +10 = 3.x +20

9.x + 14 = 3.x +20

9.x - 3.x = 20 - 14

6.x = 6

x = 6 : 6

x = 1

Vậy x = 1

12 tháng 10 2016

a) \(x:\frac{1}{2}+\frac{3}{4}=1\frac{19}{20}\)

   \(x:\frac{1}{2}+\frac{3}{4}=\frac{39}{20}\)

\(x:\frac{1}{2}=\frac{39}{20}-\frac{3}{4}\)

\(x:\frac{1}{2}=\frac{39}{20}-\frac{15}{20}\)

\(x:\frac{1}{2}=\frac{24}{20}\)

\(x=\frac{24}{20}.\frac{1}{2}\)

\(x=\frac{3}{5}\)

12 tháng 10 2016

\(x:\frac{1}{2}+\frac{3}{4}=1\frac{19}{20}\)

\(x:\frac{1}{2}=1\frac{19}{20}-\frac{3}{4}\)

\(x:\frac{1}{2}=\frac{39}{20}-\frac{3}{4}\)

\(x:\frac{1}{2}=\frac{39}{20}-\frac{15}{20}\)

\(x:\frac{1}{2}=\frac{24}{20}\)

\(x=\frac{24}{20}\times\frac{1}{2}\)

\(x=\frac{24}{40}\)

\(x=\frac{3}{5}\)